Olmesartan-associated Enteropathy with Acute Kidney Injury - Moo Jin Kang; Kyung Hwa Min; Hyung Wook Kim; Su Bum Park; Dae Hwan Kang; Cheol Woong Choi; Su Jin Kim; Hyeong Seok Nam; Dae Gon Ryu (The Korean Journal of Gastroenterology, 2022)
Olmesartan, a recently introduced angiotensin II receptor blocker for hypertension, has been reported to cause drug-induced small bowel enteropathy. The diagnosis of olmesartan-associated enteropathy (OAE) needs clinical suspicion and the exclusion of coeliac disease, as it mimics coeliac sprue. Once diagnosed, it can be completely cured with the discontinuation of olmesartan. However, due to the extremely low incidence of OAE in Korea, clinical suspicion and diagnosis may be a challenge. The authors report the first case of OAE presenting with chronic diarrhea and acute kidney injury in Korea.